The characteristics of the green internet of things and big data in building safer, smarter, and sustainable cities - Salem Alzboon, Mowafaq; Ali Al Omari, Saleh; Subhi Al-batah, Mohammad; Banikhalaf, Mustafa (International Journal of Engineering and Technology, 2019)
The worldâ€™s population development and high needs for limited goods are the results of proposing the need for further effective use of various resources and materials. Since current improvements in Information and Communication Technology (ICT) have entirely trans-formed massive regions, their use brings a negative effect on the environment and human health. Accordingly, the communityâ€™s direction is aimed at bringing a greener future where using non-renewable and raw resources and materials are minimized when energy consumption and pollution are minimized. As ICT represents a mechanism for pointing out for many different environmental issues, Green Internet of Things (G-IoT) is considered to represent an extremely important role for generating a sustainable and green place for living. Big data analysis is considered significant in performing valuable visions from large and many different G-IoT created data. The gained knowledge provides seamless forecasting, decision-making and other actions related to smart city services. Consequently, it continuously performs various developments for G-IoT technologies. Therefore, despite that the image of sustainable and smart cities is being real, G-IoT methods and visions are produced from Big data analysis that makes cities appear importantly safer, smarter and further maintainable. Accordingly, this paper attempts at summarizing the role of new technological developments and attainments of big data within the procedure of building up cities where the lifeâ€™s quality is improved with minimized pollution and further effective uses of goods. It is inferred and realized that big data and G-IoT are effectively and symbiotically functioning towards completing a sustainable and smart vision of a final city.Â Â